Inducing variety: A theory of innovation contests - Igor Letina; Armin Schmutzler (University of Zurich, Department of Economics, 2017)
This paper analyzes the design of innovation contests when the quality of an innovation depends on the research approach, but the best approach is unknown. Inducing a variety of research approaches is desirable because it generates an option value. We show that suitable contests can induce such variety. The optimal contest is a bonus tournament, where suppliers can choose only between a low bid and a high bid. We then compare the optimal contest to other commonly studied institutions, such as scoring auctions and fixed-prize tournaments.
Keywords: L14; L22; L23; 330; Contests; tournaments; auctions; diversity; innovation; procurement